Microfacies analysis and diagenetic history of Lower to Middle Eocene carbonates at Umm Russies area in the northeastern desert of Egypt - Mahmoud Abd-Elhameed; Gamal Attia; Yasser Salama; Asmaa El-Moghazy; Abdelaziz Mahmoud (Scientific Reports)
Abstract An integrated study, incorporating field observations and petrographic analysis, has been conducted on the Lower-Middle Eocene carbonates of the Umm Russies area, North Eastern Desert, Egypt. These carbonate sequence represented, from base to top, by Minia, Gebel Hof, and Observatory formations, primarily consisting of marl, dolomite, and limestone. The microfacies analysis allowed the identification of seven distinct microfacies types: bioclastic floatstone, ferruginous dolomite, bioclastic packstone, ferruginous peloidal grainstone, sandy rudstone, foraminiferal wackestone, and bioclastic packstone. These microfacies types reflect a deposition in a wide range of environments from high-energy inner ramp to low-energy middle ramp settings. The performed petrographic analysis indicates that the investigated carbonate rocks underwent significant modification through a range of diagenetic processes, such as micritization, glauconitization, and dolomitization, representing marine-phreatic, meteoric-phreatic, burial, and meteoric-vadose environments. These environments are part of three successive diagenetic stages; eogenesis, mesogenesis, and telogenesis. The relationship between diagenetic episodes and depositional settings highlights that high-energy inner ramp environments facilitated early cementation and micritization, while middle ramp conditions promoted dissolution and neomorphism. Restricted platform margin environments favored dolomitization and glauconitization. Integrating microfacies analysis with these diagenetic interpretations facilitates reconstructing paleoenvironmental conditions and provides a framework for understanding carbonate rock formation in various geological settings.